Caspase-8 Regulates Endoplasmic Reticulum Stress-Induced Necroptosis Independent of the Apoptosis Pathway in Auditory Cells - Kishino, Akihiro (Int J Mol Sci, 2019)
The aim of this study is to elucidate the detailed mechanism of endoplasmic reticulum (ER) stress-induced auditory cell death based on the function of the initiator caspases and molecular complex of necroptosis. Here, we demonstrated that ER stress initiates not only caspase-9-dependent intrinsic apoptosis along with caspase-3, but also receptor-interacting serine/threonine kinase (RIPK)1-dependent necroptosis in auditory cells. We observed the ultrastructural characteristics of both apoptosis and necroptosis in tunicamycin-treated cells under transmission electron microscopy (TEM). We demonstrated that ER stress-induced necroptosis was dependent on the induction of RIPK1, negatively regulated by caspase-8 in auditory cells. Our data suggested that ER stress-induced intrinsic apoptosis depends on the induction of caspase-9 along with caspase-3 in auditory cells. The results of this study reveal that necroptosis could exist for the alternative backup cell death route of apoptosis in auditory cells under ER stress. Interestingly, our data results in a surge in the recognition that therapies aimed at the inner ear protection effect by caspase inhibitors like zVAD-fmk might arrest apoptosis but can also have the unanticipated effect of promoting necroptosis. Thus, RIPK1-dependent necroptosis would be a new therapeutic target for the treatment of sensorineural hearing loss due to ER stress.